ANALYSIS OF EMOTIONAL INTELLIGENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Nashrudin Setiawan; Renny Maisyarah; Rosina Harahap (Universitas Airlangga, 2020)
This study aims to determine whether emotional intelligence partially has a positive and significant effect on employee performance at PT Jaya Teknik Indonesia. Does work discipline partially have a positive and significant effect on employee performance at PT Jaya Teknik Indonesia. Does emotional intelligence affect employee performance through organizational commitment to PT Jaya Teknik Indonesia. Does work discipline affect employee performance through organizational commitment to PT Jaya Teknik Indonesia. The data analysis technique used is the associative method with the help of the SPSS version 16.0 program. This study uses the classic assumption test, multiple linear regression analysis, t test, F test, determination test and path analysis test. The population in this study were all employees of PT Jaya Teknik Indonesia, and a sample of 60 respondents. Taking primary data using a questionnaire. The results showed that emotional intelligence partially had a positive and significant effect on employee performance at PT Jaya Teknik Indonesia. Does work discipline partially have a positive and significant effect on employee performance at PT Jaya Teknik Indonesia. Does emotional intelligence affect employee performance through organizational commitment to PT Jaya Teknik Indonesia. Does work discipline affect employee performance through organizational commitment to PT Jaya Teknik Indonesia Does work discipline partially have a positive and significant effect on employee performance at PT Jaya Teknik Indonesia. Does emotional intelligence affect employee performance through organizational commitment to PT Jaya Teknik Indonesia. Does work discipline affect employee performance through organizational commitment to PT Jaya Teknik Indonesia Does work discipline partially have a positive and significant effect on employee performance at PT Jaya Teknik Indonesia. Does emotional intelligence affect employee performance through organizational commitment to PT Jaya Teknik Indonesia. Does work discipline affect employee performance through organizational commitment to PT Jaya Teknik Indonesia.